Strengthening Islamic Character Education among Students in the Era of Digital Disruption - Ryan Radjendra; Syifa Adilla Zahra; Wiwin Sunita; Syifaul Karima; Sunariyah Sunariyah; Chairul Anwar (Ahlussunnah: Journal of Islamic Education, 2026)
The rapid development of digital technology has significantly transformed social life and educational practices, creating both opportunities and challenges for strengthening Islamic character education. Digital disruption has led to various issues, including moral degradation, weakening internalization of Islamic values, and exposure to unfiltered information, particularly among the younger generation. This study aims to examine strategies for strengthening Islamic character education in the context of digital disruption. This research employs a qualitative approach using content analysis of relevant sources, including books, scholarly articles, and prior studies. The findings reveal that strengthening Islamic character requires integrative strategies, including the internalization of Quranic and Sunnah values, role modeling by educators, the utilization of digital technology as a medium for moral education, and collaboration among educational institutions, families, and communities. This study contributes by proposing a conceptual framework for Islamic character education that is adaptive to digital transformation while maintaining its spiritual and moral foundations.